II - Insulin processing in mitochondria - Camberos, Maria del Carmen (2016)
Our objective was to know how insulin is processing in mitochondria; if IDE is the only participant in mitochondrial insulin degradation and the role of insulin degradation on IDE accumulation in mitoplasts. Mitochondria and its fractions were isolated as described by Greenwalt. IDE was purified and detected in immunoblot with specific antibodies. High insulin degradation was obtained through addition to rat’s diet of 25ï¿½g/rat of apple and 10ï¿½g/rat of hard-boiled eggs, 3ï¿½days a week. Mitochondrial insulin degradation was assayed with 5ï¿½% TCA, insulin antibody or Sephadex G50 chromatography. Degradation was also assayed 60ï¿½min at 37ï¿½ï¿½C in mitochondrial fractions (IMS and Mx) with diet or not and without IDE. Degradation in fractions precipitated with ammonium sulfates (60–80ï¿½%) were studied after mitochondrial insulin incubation (1ï¿½ng. insulin during 15ï¿½min, at 30ï¿½ï¿½C) or with addition of 2.5ï¿½mM ATP. Supplementary diet increased insulin degradation. High insulin did not increase mitoplasts accumulation and did not decrease mitochondrial degradation. High insulin and inhibition of degradation evidence insulin competition for a putative transport system. Mitochondrial incubation with insulin increased IDE in matrix as observed in immunoblot. ATP decreased degradation in Mx and increased it in IMS. Chromatography of IMS demonstrated an ATP-dependent protease that degraded insulin, similar to described by Sitte et al. Mitochondria participate in insulin degradation and the diet increased it. High insulin did not accomplish mitochondrial decrease of degradation or its accumulation in mitoplasts. Mitochondrial incubation with insulin increased IDE in matrix. ATP suggested being a regulator of mitochondrial insulin degradation.